User:Psellier/My Sandbox

From WikiEducator
Jump to: navigation, search

Solving Quadratic Equations

Icon objectives.jpg
After working through this section you will:
  • find the x values that satisfy a given quadratic equation

The L4C Logo

Quadratic Equations

Icon discussion.gif
What does it mean to solve a quadratic equation?

A quadratic equation is an equation of the form ax2+bx+c=0. For example, 2x2-7x-15=0.

So, what does it mean to solve a quadratic equation?

Solving a quadratic equation means finding those values of x that make the equation true.

For example, solving 6x2+10x+3=7 means finding the values of x that make this equation true.

If x=-2, 6(-2)2+10(-2)+3=7

If x=1/3,6(1/3)2+10(1/3)+3=7

Only these two values of x: -2 and 1/3 make this equation true, so these are the solutions to the equation 6x2+10x+3=7.

How do I find these values of x that make the equation true?

Before we discuss that, there is an important theorem we need to revisit:

Icon preknowledge.gif


The Zero Factor Principle

If a x b = 0 then

  • a=0
  • b=o

or both a and b are zero.

Now we have reviewed the Zero Factor Principle, we can continue our exploration into solving quadratic equations. We see now that we can solve any factor-equation of the form ab=0.

Icon activity.jpg
Solving a Quadratic Equation

We will look at a specific example of a factorable quadratic equation 6x2+x-15=0 where a = 6, b = 1 and c = -15. Notethe sign on the number must be included.

ax2+bx+c=0 6x2+x-15=0
Step 1: Multiply a by c. a x c = ac 6 x -15 = -90
Step 2: Find the factors of ac that add to give b. -90 = -9 x 10; -9 + 10 = 1
Step 3: Rewrite the equation, represent b as the

sum of the two factors you just found.

Factor the equation by grouping. 3x(2x-3)+5(2x-3)=0
This equation now has two terms that

have a common factor of (2x-3), factor again.


Now you have a factor-equation of the form a x b = 0: (2x-3)(3x+5)=0

Here we will use the Zero Factor Principle, so

  • 2x-3 = 0, and so solving for x, x = 3/2
  • 3x+5 = 0, and so solving for x, x = -5/3